Biological approaches to controlling pollutants - Kumar, Sunil, Ph. D.; Hashmi, Muhammad Zaffar (Advances in pollution research., 2022)
"Biological Approaches to Controlling Pollutants, the latest release in the Advances in Pollution Research series, is a comprehensive guide on the most up-to-date biological methods for remediation of pollutants across a variety of industries, with consideration for the advantages, disadvantages and applications of each method. Considering the increasing levels of pollution and contaminated sites worldwide from high population growths and industrial expansion, the most recent advances in biological remediation techniques is an important field of study and one in which researchers need the most cutting-edge methodologies. This book is a necessary read for environmental scientists, along with postgraduates, academics and researchers working in the area of environmental pollution. It will also be of interest to environmental engineers and any other practitioners who need to evaluate the latest advances in biotechnological control of pollutants."--